A mocinha do mercado central: uma leitura bakhtiniana - Queiroz, Daniela Nascimento Andrade (2018)
In Bakhtinian philosophy, dialogue is the fundamental concept of the exercise of language as dialogic relations, as categories of analysis, are extralinguistic relations woven and interwoven without discourse. The novel is a literary genre conducive to the analysis of dialogical relations whether through intense use of the compositionally expressed dialogues, either by the presence of the inner dialogue that is deserved by Mikhail Bakhtin intense studies. Starting from the perspective, this work was to search in Brazilian children's literature a copy of a novel that allows us to investigate the modes of realization of the dialogical relations in their different manifestations and their contribution to an organization of the romanesque genre. The general purpose of this work was to analyze in the light of the bakthiniano dialogue, the romance of children's literature, A mocinha do Mercado Central, Stella Maris Rezende. The specific objective was to investigate the mode of dialogic relations and the chronotope of the narrative plot in the heroine's journeys in search of her own identity. A theoretical foundation used as reflections and discoveries of Bakhtin and his Circle (1988; 1993; 2003; 2004) on dialogue, as well as the studies of commentators of his work, such as Brait (2005, 2010), Fiorin (2016) and Morson and Emerson (2008). The methodology used was descriptive and qualitative and a bibliographical survey of the works of Bakhtin on dialogism, discursive genres and chronotope for the realization of the dialogical analysis of the corpus. The research proved that A mocinha do Mercado Central is a novel of youth literature, which in its construction as a work of fiction around the search for identity by a young heroine, son of an unknown father, organized around an intense dialogic exchange with young readers who can experience a shock of problem recognition and very appropriate solutions in their age range.